A Halal Characteristic of Behavioral Intention and Its Implication to the Purchase - Nasution, Siti Wardah Pratidina; Sa'diah, Kamilah; Zakaria, Nor Balkish; Liswandi, Liswandi (Penerbit Goodwood, 2025)
Purpose: This study proposes to examine and prove empirically about influence of Halal Characteristic consist of Halal Awareness and Halal Logo on the Behavioral Intention of Halal Food Product. Methodology/Approach: The research period taken throughout 2024 until the end of the year has the potential to be biased when obtaining information from respondents. Moreover, the extent of the study is consumers in Medan City, Indonesia. Sampling criteria use a purposive technique. Results/Findings: The halal characteristic from awareness and logo have a positive and insignificant influence on Behavioral Intention and Purchase Intention of Halal Food. Behavioral Intention has a positive and significant influence on the Behavioral Intention and Purchase Intention of Halal Food in Medan City, Indonesia. Conclusions: Halal awareness and logos have no significant effect, while behavioral intention strongly drives purchase intention. Broader scope and added variables are recommended for future research. Limitations: The study period taken throughout 2024 until the end of the year has the potential to be biased when obtaining information from respondents. In addition, the scope of this study is limited to only consumers in Medan City, Indonesia. Contribution: This study is expected to be beneficial for consumers who want to take an attitude, desire, or intention to buy halal food. Then, an entrepreneur can use this as information in evaluating their business strategies.